2011
DOI: 10.1161/circulationaha.110.012211
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Splicing Variant Calcineurin Aβ1 Improves Cardiac Function After Myocardial Infarction Without Inducing Hypertrophy

Abstract: Calcineurin Aβ1 shows a unique mode of action that improves cardiac function after myocardial infarction, activating different cardioprotective pathways without inducing maladaptive hypertrophy. These features make CnAβ1 an attractive candidate for the development of future therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 27 publications
0
59
0
Order By: Relevance
“…Similar to the C-terminal truncated CnA* proteins, the CnAβ1 variant is constitutively active. Remarkably, however, a cardiomyocyte-specific α MHC-Cn β 1 transgene does not provoke hypertrophy but exerts beneficial effects following myocardial infarction by promoting vascularization [34, 35]. How this is accomplished is not yet understood, however, interesting data is emerging that suggests CnAβ1 may be important for proper localization and signaling of mTORC2 complexes [34, 36].…”
Section: Calcineurin Structure and Regulationmentioning
confidence: 99%
“…Similar to the C-terminal truncated CnA* proteins, the CnAβ1 variant is constitutively active. Remarkably, however, a cardiomyocyte-specific α MHC-Cn β 1 transgene does not provoke hypertrophy but exerts beneficial effects following myocardial infarction by promoting vascularization [34, 35]. How this is accomplished is not yet understood, however, interesting data is emerging that suggests CnAβ1 may be important for proper localization and signaling of mTORC2 complexes [34, 36].…”
Section: Calcineurin Structure and Regulationmentioning
confidence: 99%
“…We have previously shown that CnAβ1 regulates AKT phosphorylation (Felkin et al, 2011;López-Olañeta et al, 2014). To investigate whether CnAβ1 is controlling this pathway during mESC differentiation we knocked down CnAβ1 and induced the mESCs to differentiate to mesoderm.…”
Section: Cnaβ1 Regulates Mesoderm Specification Through Akt Gsk3 Andmentioning
confidence: 99%
“…In addition to known CnA interacting proteins like CnB (Felkin et al, 2011), we identified the interaction between CnAβ1 and Cog8, a protein enriched mainly in the external Golgi as well as other intracellular membranes that is involved in the interaction with the Cog and SNARE complexes (Laufman et al, 2013;Willett et al, 2013;Willett et al, 2014) (Table S4). To validate this interaction, we transfected cells with GFP-CnAβ1 chimeras and carried out immunoprecipitation and colocalization experiments.…”
Section: Cog8 Drives the Localization Of Cnaβ1 To The Golgi Apparatusmentioning
confidence: 99%
“…Cardiomyocyte hypertrophy can be estimated by measuring cell cross-sectional area after staining with wheat germ agglutinin [74]. Myocardial expression of HF markers such as brain natriuretic peptide (BNP), α-skeletal, actin, and, in some species, β-myosin heavy chain can be determined by qRT-PCR or by Western blot [75,76]. Expression of inflammation and fibrosis-related markers can also be quantified in this manner [77].…”
Section: Tissue Remodeling Fibrosis and Inflammationmentioning
confidence: 99%